Initiatives and challenges of a chemical industries council in a developing country: the case of Malaysia. (1st January 2015) - Lee, Khai Ern; Mokhtar, Mazlin; Goh, Choo Ta; Singh, Harminder; Chan, Pek Wan
Abstract: While the Malaysian chemicals industry has been progressively growing over the past few decades, the industry associations had not been actively engaged with one another. The Chemical Industries Council of Malaysia was established to form a stronger and more cohesive representation from other sub-sectors of the industry such as oleochemicals, industrial gases, petrochemicals, paints, coating resins, fertilizers, biodiesel and pesticides, as well as their respective chemical traders, distributors and other service providers. Among its initiatives is the Responsible Care programme which has proven to be a very useful tool in promoting responsible practices among signatory companies that protect the environment, human health and safety. While the chemicals industry and related industries have adopted most of the responsible best practices to reduce their environmental impact, participation from small and medium enterprises has been low. This paper aims to provide an overview of the initiatives of the Chemical Industries Council of Malaysia, and assess its current position with regard to providing environmental, health and safety services to its members in view of the expanding global chemicals sector and the challenges it poses. It will also identify the main challenges faced by the chemicals industry, and propose measures to overcome them for the future competitiveness and sustainability of the chemicals industry at both regional and international levels. Highlights: The CICM forms a cohesive representation of the chemicals industry. The Responsible Care program is the flagship initiative of the CICM. The Responsible Care program promotes responsible and clean production practices. The Responsible Care program needs more participation from Small and Medium Enterprises.